Boost in the thermal stability, ionic conductivity and director relaxation frequency in the composite of liquid crystal and functionalised multi-walled carbon nanotubes. Issue 3 (19th February 2021) - Patro, Ch Kartikeswar; Verma, Rohit; Garg, Aakrati; Dhar, Ravindra; Dabrowski, Roman
ABSTRACT: In the present work, we have prepared a liquid crystal-carbon nanotube (LC-CNT) composite by dispersing a low concentration of carboxylic group (-COOH) functionalised multi-walled CNTs (MWCNTs) in a liquid-crystal 6CHBT and studied in detail the alterations in thermal and electrical parameters. Thermodynamic studies reveal that transition processes are becoming fast due to the dispersion of MWCNTs. The change in the behaviour of transitions is credited to the reduction in ionic impurities owing to the ion trapping characteristic of CNTs. The isotropic liquid to nematic transition temperature of the composite system is increasing for the exothermic cycle as compared to that of the pure sample. The average transition enthalpies and entropies for various transitions of the composite system are increasing as compared to those of the virgin sample. Longitudinal component of the permittivity and dielectric anisotropy of the composite system is slightly reduced as compared to those of the virgin sample. Relaxation frequencies of an observed relaxation mechanism corresponding to the rotation of molecules about their short axes of the composite system are enhanced as compared to the undispersed sample. Total ionic conductivity of the composite system is boosted as compared to those of the pure sample. Graphical abstract: uf0001